Self-evaluation of the modern languages major focused in two factors: students and resources at the foreign languages department, University of El Salvador, 2012 - Pineda Campos, Elba Beatriz
The evaluation of the Modern Languages Major is focused on two main aspects, “Students and Resources”, whose purpose is to determine the existence of academic quality standards and/or minimum quality features in the aspects above mentioned. To perform this evaluation the program evaluation guidelines published by CSUCA and SICEVAES were used. This document provides guidance to Central American Universities toward planning and implementing evaluation processes aiming at improving their different academic programs.